الوقف الدولي والقوة الناعمة بالإشارة إلى مؤسسة زايد للأعمال الخيرية والإنسانية :b - سقاف، أحمد علوي الشيخ هود (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
This study explores aspects of Waqf Studies, namely, learning more about the possibility of employing waqf as a soft power and studying the hidden capabilities of this power, through its analysis and method of employment, in order to determine its impact on the beneficiary and how it guides the beneficiary intellectually. The research aims to shed light on the contributions of waqf to the Islamic civilization, the historical development in its relationship with the state practically and legislatively. It also aims to develop a deeper understanding of the concept of soft power, its use in the third sector, international endowment and international politics, the extent to which soft power exists in the Zayed Foundation model, and the possibility of using and developing it, and to clarify the problems relating to Islamic jurisprudence (fiqh). The researcher employed the following methods: the historical method to show the development of the waqf system and its civilizational roles in the thriving of knowledge and science, as well as its intellectual orientation; the descriptive method to study soft power and the reasons that led to its emergence and its uses in international politics; the inductive method in studying the institutional approach of the Sheikh Zayed Foundation and surveying and examining the Foundation's projects, their quantitative and qualitative diversity, their goals, and the international endowments that it established; and the analytical method in studying the hidden possibilities and capabilities of soft power in waqf, analysing them and how they are being employed. In conducting this study, the researcher relied on his knowledge of the Sheikh Zayed Foundation via his communication and various interactions with a number of the foundation's directors and visits to some of its projects inside and outside the country. The most important findings of the research are that waqf possesses sources of soft power, and some Western international endowment institutions have benefited from this feature in influencing other societies. Likewise, it has been employed historically to effect soft change; because of the continued and lasting impact it has with the continued and lasting existence of the waqf. This study further indicates that despite the interest of countries in international aid within the parameters of their respective foreign policies and their interest in soft power, they suffer from shortcomings in many aspects, which the international awqaf (pl. of waqf) can address in part. If the founder or donor of these awqaf lays out the conditions in an optimal manner as such that they appear in a cooperative manner, consistent with the aims and objectives specified and is able to implement them with the proper mechanisms in place, then it is possible for these awqaf to be employed as a soft power.